Upaya Meningkatkan Hasil Belajar Siswa dengan Metode Iqro’ pada Mata Pelajaran BTA di SD Negeri 2 Lumbungkerep Wonosari Ta.2021/2022 - Nita Nur Samsiyah; Uswatun Khasanah; M. Fatchurrohman (Departement of Mathematics Education, 2023)
Based on the results of research observations, in the odd semester learning outcomes for BTA subjects in 2021/2022, there are some students who have not completed due to variations in teaching styles that do not support student activity in the learning process that still uses the old learning method. From this, the formulation of the problem in th is study is: